Clinical trial of a probiotic and herbal supplement for lung health - Wenger, Nancy M.; Qiao, Luhua; Nicola, Teodora; Nizami, Zoha; Martin, Isaac; Halloran, Brian A.; Tanaka, Kosuke; Evans, Michael; Xu, Xin; Dinan, Timothy G.; Kakilla, Charles; DunnGalvin, Gillian; et al. (Frontiers in Nutrition, 2023)
Introduction: Dysbiosis of the gut microbiome may augment lung disease via the gut-lung axis. Proteobacteria may contribute to tissue proteolysis followed by neutrophil recruitment, lung tissue injury, and perpetuation of chronic inflammation. To study the effects of probiotics across the gut-lung axis, we sought to determine if a Lactobacillus probiotic and herbal blend was safe and well-tolerated in healthy volunteers and asthmatic patients. Methods: We conducted a 1-month randomized, open-label clinical trial in Cork, Ireland with healthy and asthmatic patients who took the blend twice a day. The primary endpoint was safety with exploratory endpoints including quality of life, lung function, gut microbiome ecology, and inflammatory biomarkers. Results: All subjects tolerated the blend without adverse events. Asthmatic subjects who took the blend showed significant improvements in lung function as measured by forced expiratory volume and serum short chain fatty acid levels from baseline to Week 4. The gut microbiome of asthmatic subjects differed significantly from controls, with the most prominent difference in the relative abundance of the proteobacteria Escherichia coli. Administration of the probiotic maintained overall microbial community architecture with the only significant difference being an increase in absolute abundance of the probiotic strains measured by strain-specific PCR. Conclusions: This study supports the safety and efficacy potential of a Lactobacillus probiotic plus herbal blend to act on the gut-lung axis. However, due to the lack of a control group, a longer blinded, placebo-controlled study will be warranted to confirm the efficacy improvements observed in this trial.